Flood loss assessment in the Kota Tinggi - Tam, Tze Huey (2013)
Malaysia is free from several destructive and widespread natural disasters but frequently affected by floods, which caused massive flood damage. In 2006 and 2007, an extreme rainfall occured in many parts of Peninsular Malaysia, which caused severe flooding in several major cities. Kota Tinggi was chosen as study area as it is one the seriously affected area in Johor state. The aim of this study is to estimate potential flood damage to physical elements in Kota Tinggi. The flood damage map contains both qualitative and quantitative information which corresponds to the consequences of flooding. This study only focuses on physical elements. Three different damage functions were adopted to calculate the potential flood damage and flood depth is considered as the main parameter. The adopted functions are United States, the Netherlands and Malaysia. The estimated flood damage for housing using United States, the Netherlands and Malaysia was RM 350/m2 RM 200/m2 and RM 100/m2 respectively. These results successfully showed the average flood damage of physical element. Such important information needed by local authority and government for urban spatial planning and aiming to reduce flood risk.